Penggunaan Aplikasi Digital Weverse sebagai New Media Interaksi antara Artis/Idol K-Pop dengan Para Penggemarnya - Putra, Wahyu Ferdiansyah; Febriana, Poppy (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to see how the role of the Weverse digital application as a New Media in the interaction relationship between K-Pop Artists or Idols and their fans. And understand what are the effects of using the Weverse digital application. In conducting this research, the researcher uses the basis of Media Dependency Theory. The thing that underlies the use of media dependency theory in this study is because the theory explains that the more a person depends on a media to meet their needs, the more important the media becomes for that person. The research method used is a qualitative method by distributing questionnaires or questionnaires to the respondents who use the application. The results of this study, with the Weverse digital application as a new media, will make it easier for fans to interact with K-Pop Artists/Idols.